Optimalisasi Pengelolaan Keuangan Pondok Pesantren untuk Mewujudkan Kemandirian Ekonomi - Norman, Efrita; Sukarnoto, Toto; Cahyono, Heru; Ridwan, Mohammad (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
Islamic boarding schools (pesantren) play a vital role in shaping morally upright and knowledgeable individuals while also serving as centers of social and economic activities within local communities. However, many pesantren struggle to achieve financial independence due to inadequate financial management practices. This community service project aimed to address these gaps by providing comprehensive financial management training to pesantren administrators, with the goal of fostering economic self-reliance. The methodologies employed included participatory approaches, workshops, and follow-up mentoring to ensure the effective application of financial management principles. As a result, participating pesantren were able to implement improved financial management systems, including better cash flow monitoring, structured financial reporting, and transparent budgeting. These changes led to enhanced transparency, accountability, and decision-making in financial matters. Furthermore, the project assisted pesantren in identifying and developing independent business ventures such as agriculture, crafts, and food production, thus providing alternative revenue streams. The outcomes demonstrated that with proper financial management training and support, pesantren could move towards economic sustainability, reducing their dependence on external donations. This program contributes to the broader field by demonstrating the significant impact of structured financial management in educational institutions.